DEVELOPMENT OF STUDENT ACTIVITY SHEET (SAS) USING MIND MAPPING STRATEGIES TO IMPROVE CREATIVE THINKING SKILLS ON ATOMIC MATERIALS AND NANOTECHNOLOGY - Nuha, Shinta Taqiyyah Nabilah; Mitarlis (Universitas Negeri Surabaya, 2025)
This study aims to obtain a suitable SAS to improve students' creative thinking skills. This type of research includes research and development. The development of the model used refers to the 4-D model but is only limited to the stages of determination, design, and development. Trial activities were carried out on 34 students of class XE-3. The feasibility of the developed SAS is guided by validity, practicality, and effectiveness. Validation was carried out by expert validators with scores determined based on the mode value. The results of the study showed the feasibility of the teaching module in terms of content validity and construct validity which obtained modes 4 and 5 in each aspect with valid and very valid categories so that overall the teaching module obtained a mode ≥4 and was declared valid. The results of the practicality analysis were seen from the student response questionnaire and observations of student activities. The percentage of practicality based on the student response questionnaire and student observations was obtained at 92.01% with a very practical category. Meanwhile, the observation results of student activities obtained relevant activities at meeting 1 of 97.62% and meeting 2 97.37%. From the three percentages obtained the percentage of relevant participant activities was increased by 97.5% so that it can be said that the SAS was developed very practically. The results of the analysis of the effectiveness of SAS were measured based on the increase in students' creative thinking skills through the pretest and posttest mind map as well as questions about understanding creative thinking skills on chemical bonding material with N-gain values obtained respectively of 0.73 and 0.72 with a high category. Based on the results of validity, practicality and effectiveness, the mind map strategy teaching module is suitable for use as a learning tool to improve creative thinking skills on atomic and nanotechnology materials.